2022
DOI: 10.1155/2022/1250755
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Clinical Effect of Metronidazole Vaginal Effervescent Tablet Combined with Flavescentis Sophora Suppository in the Treatment of Trichomonas Vaginitis

Abstract: For the treatment of trichomonas vaginitis, a combination therapy of metronidazole vaginal effervescent tablet combined with Flavescentis Sophora suppository is proposed. The patients diagnosed with trichomonas vaginitis are divided into the conventional treatment group and the joint group. The conventional group is treated with metronidazole vaginal effervescent tablets, and the joint group is treated with metronidazole vaginal effervescent tablets combined with sophora bolt. Both groups are treated for 3 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%